2013
DOI: 10.1128/mcb.00069-13
|View full text |Cite
|
Sign up to set email alerts
|

EED and KDM6B Coordinate the First Mammalian Cell Lineage Commitment To Ensure Embryo Implantation

Abstract: The first mammalian cell lineage commitment is the formation of the trophectoderm (TE) and the inner cell mass (ICM) lineages during preimplantation development. Proper development of the TE and ICM lineages is dependent upon establishment of specific transcriptional programs. However, the epigenetic mechanisms that functionally contribute to establish TE-and ICM-specific transcriptional programs are poorly understood. Here, we show that proper development of the TE and ICM lineages is coordinated via combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 60 publications
3
53
0
Order By: Relevance
“…The regulation of Cdx2 expression in early embryos and other developmental contexts is mediated by transcriptional and epigenetic mechanisms (Chen et al, 2009;Home et al, 2009Home et al, , 2012Yeap et al, 2009;Yuan et al, 2009;Saha et al, 2013;Rayon et al, 2014). Several key regulatory regions are present in Cdx2 (Wang and Shashikant, 2007;Benahmed et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of Cdx2 expression in early embryos and other developmental contexts is mediated by transcriptional and epigenetic mechanisms (Chen et al, 2009;Home et al, 2009Home et al, , 2012Yeap et al, 2009;Yuan et al, 2009;Saha et al, 2013;Rayon et al, 2014). Several key regulatory regions are present in Cdx2 (Wang and Shashikant, 2007;Benahmed et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…H3K27Me3 is another histone modification implicated in transcriptional repression of TE-specific genes within the ICM lineage cells (Saha, et al 2013). H3K27Me3 modification is regulated by polycomb repressor 2 (PRC2) complex.…”
Section: Histone Modifications and Trophoblast Developmentmentioning
confidence: 99%
“…Recently, it was reported that proper regulation of H3K27Me3 incorporation at TE-specific genes is important during preimplantation lineage development. Loss of H3K27Me3 incorporation at the TE-specific genes like Cdx2 and Gata3 is essential for proper development of the TE lineage and embryo implantation (Saha, et al 2013). Analyses in mouse embryos indicated that coordinated regulation of lysine-specific histone demethylase 6B and embryonic ectoderm development (EED), a core component of PRC2, ensures loss of He3K27Me3 incorporation at the chromatin domains of TE/TSC-specific genes (Rugg-Gunn, et al 2010, Saha, et al 2013).…”
Section: Histone Modifications and Trophoblast Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In conjunction with the HIPPO pathway, OCT4 and CDX2 negatively regulate one another's expression in the ICM and trophoblast lineages via binding to each other's promoters and cooperating with ERG-associated protein with SET domain (ESET) and BRG1 (Brahma-related gene 1), a chromatin-remodeling protein, to block transcription (13)(14)(15). Other epigenetic modifiers, such as embryonic ectoderm development (EED) and lysine (K)-specific demethylase 6B (KDM6B), work in opposition to restrict Cdx2 and Gata3 expression to the trophoblast lineage (16). Altogether, these studies demonstrate that ICM and trophoblast lineage development is regulated by overlapping transcriptional and epigenetic mechanisms.…”
mentioning
confidence: 99%